Comparative Evaluation of YOLO Models for Gauge Detection - (:unkn) unknown (IEEE, 2024)
In various industries, accurate gauge measurement is crucial for maintaining safety and equipment integrity, particularly in hazardous environments with flammable, corrosive, or toxic substances. Ensuring precise detection is essential to avoid accidents...
Keywords: Detección de objetos; YOLO